Parliamentary Work, Re-Selection and Re-Election: In Search of the Accountability Link. Issue 4 (31st January 2018) - Papp, Zsófia; Russo, Federico
Abstract: Parliamentarians greatly differ with regard to the amount and quality of their work in parliament. Students of legislator behaviour mostly view Members of Parliament (MPs) as 'single-minded seekers of re-election', which is often argued to be the motivation for carrying out various activities. However, less attention has been paid to what extent MPs' efforts pay off at the next elections. The special section introduced here addresses the question if the type and volume of parliamentary activities carried out by legislators have any effect on their electoral prospects. In other words, do parties and voters take MPs' activity record into account when deciding on the re-election and the re-selection of an incumbent? To shed some light on this topic, we bring together students of legislative and electoral behaviour from all parts of Europe. Our general aim is to disentangle the necessary conditions for personal accountability to work in representative democracies.